THE ASSOCIATION BETWEEN JOB STRESS RELATED FACTORS AND JOB PERFORMANCE AT XYZ’S ORGANIZATION - Siti Nurul Akma Ahmad; Nor Maslia Rasli Samudin; Nur Idayu Badrolhisam; Nurhafizah Mohd Zolkapli; Siti Norashikin Bashirun; Farah Shazlin Johari (International Journal of Accounting, Finance and Business, 2021)
This study is conducted to examine the association of job stress-related factors and employees' job performance at XYZ’s Organization. There are three job-related stress factors used to examine the association which are role ambiguity, workload, and role conflict. The data were collected through a set of questionnaires and involved all employees in the organization, however, only 52 responses were completed and valid. The study found that all the respondents had to experience stress from those three variables mentioned and somehow affecting their job performance. As a result, the study concludes that role ambiguity and role conflict have a positive relationship to the employee’s job performance. While for workload, it can be concluded that the factor is not influencing performance since it has a negative correlation with job performance. The study recommends that employees should clearly define their roles and objectives to minimize role ambiguity and role conflict which can lead to poorer performance in an organization.